The Complexity of KIT Gene Mutations and Chromosome Rearrangements and Their Clinical Correlation in Gastrointestinal Stromal (Pacemaker Cell) Tumors - Andersson, Johanna (American Society for Investigative Pathology, 2002)
Gastrointestinal stromal (pacemaker cell) tumors (GIST/GIPACTs) are frequently associated with activating KIT mutations, primarily of exon 11 and rarely of exons 9 and 13, as well as certain chromosome rearrangements. Reports regarding the frequency and prognostic significance of KIT mutations are conflicting and few cases have been completely sequenced. Furthermore, there are few detailed analyses of chromosome alterations in GIST/GIPACTs. In a detailed analysis of 14 GIST/GIPACTs from 12 patients, we found a wider spectrum of KIT mutations than previously reported, including 11 different in-frame mutations involving exons 11, 14, and 15. No mutations were detected in four malignant tumors. The shorter (GNNK−) KIT isoform was preferentially expressed. Cytogenetic and spectral karyotype analyses of 10 tumors revealed clonal abnormalities in eight tumors; the most common were terminal 1p deletions and losses of chromosomes 14 and/or 22. Neither KIT mutation status nor chromosome aberrations correlated with tumor phenotype or clinical behavior in our series. Collectively, these findings indicate that the role of KIT mutations and chromosomal rearrangements in the pathogenesis of GIST/GIPACTs are more complex than previously recognized.